The National Disability Insurance Scheme in an Urban Context: Opportunities and Challenges for Australian Cities. Issue 1 (2nd January 2019) - Wiesel, Ilan; Whitzman, Carolyn; Gleeson, Brendan; Bigby, Christine
ABSTRACT: The NDIS will directly affect the lives of close to half a million people with a disability as well as significantly wider impacts on Australian cities. This review paper examines the urban policy and practice context for the NDIS, focusing specifically on housing, employment, governance, mainstream services (particularly health and education) and multiculturalism. Although the current Australian urban condition is hardly ideal for the implementation of such an ambitious scheme, the funding provided by the NDIS, coupled with appropriate adjustments to mainstream urban policy, can make important contributions to the social, cultural and economic thriving of Australian cities.